Emerging global cities : origin, structure, and significance - Portes, Alejandro, 1944-; Armony, Ariel C. (Columbia University Press, 2023)
'Certain cities-most famously New York, London, and Tokyo-have been identified as "global cities," whose function in the world economy transcends national borders. Without the same fanfare, formerly peripheral and secondary cities have been growing in importance, emerging as global cities in their own right. The striking similarity of the skylines of Dubai, Miami, and Singapore is no coincidence: despite following different historical paths, all three have achieved newfound prominence through parallel trends. In this groundbreaking book, Alejandro Portes and Ariel C. Armony demonstrate how the rapid and unexpected rise of these three cities recasts global urban studies. They identify the constellation of factors that allow certain urban places to become "emerging global cities"-centers of commerce, finance, art, and culture for entire regions. The book traces the transformations of Dubai, Miami, and Singapore, identifying key features common to these emerging global cities. It contrasts them with "global hopefuls," cities that, at one point or another, aspired to become global, and analyzes how Hong Kong is threatened with the loss of this status. Portes and Armony highlight the importance of climate change to the prospects of emerging global cities, showing how the same economic system that propelled their rise now imperils their future. Emerging Global Cities provides a powerful new framework for understanding the role of peripheral cities in the world economy and how they compete for and sometimes achieve global standing"-- Provided by publisher.
Keywords: Megacities.; Urbanization.; City planning.; Mégalopoles.; Urbanisation.; megalopolises.; urbanization.; ARCHITECTURE / Urban & Land Use Planning; City planning; Megacities; Urbanization